Comparative evaluation of different carbon sources supply on simultaneous production of lipid and carotene of Rhodotorula glutinis with irradiation and the assessment of key gene transcription. (September 2019) - Gong, Guiping; Liu, Luo; Zhang, Xu; Tan, Tianwei
Highlights: Different carbon sources were applied to culture R. glutinis with irradiation. Enhancement of lipid and carotene production from various substrates by irradiation. Enhanced unsaturated fatty acids by irradiation with different carbon sources. Key genes transcription level on different substrates with irradiation was evaluated. Abstract: To investigate the feasibility of simultaneously enhancing lipid and carotene production by irradiation with different carbon sources, a strategy by controlling the carbon sources supply were selected to culture Rhodotorula glutinis under the irradiation condition. The results demonstrated that the irradiation indeed enhanced cell growth, lipid and carotene production with different carbon sources supply . Besides, the fatty acids profiling as revealed by more unsaturated fatty acids (mainly C16:1, C18:2 and C18:3) and less saturated fatty acids (C18:0, C22:0 and C24:0) were found during the process of irradiation. Compared with the control, the increase of the transcription levels in genes connected with substrates assimilation, lipid production and carotene accumulation were observed under the irradiation condition. The results suggest the possibility of using irradiation as an effective strategy to increase the production of both lipid and carotene with the controlled carbon sources supply.